THE PRIMARY CAUSES OF RISK EMERGENCE IN SMALL BUSINESSES - Ismoilova Zebiniso Sarvarbek qizi, (TADQIQOTLAR, 2026)
Abstract.  This  paper  explores  the  primary  causes  of  risk  emergence  in  small businesses.  Due  to  their  limited  resources  and  heightened  vulnerability  to  external factors, small enterprises are particularly susceptible to various risks that can hinder their  stability  and  growth.  The  study  identifies  key  factors  contributing  to  risk emergence,  including  economic  instability,  lack  of  financial  and  human  resources, insufficient strategic planning, low adaptability to market changes, and regulatory or legal uncertainties. Understanding and categorizing these risk factors can help develop effective risk management strategies to enhance the resilience and long-term viability of small businesses.